2022
DOI: 10.1038/s41467-022-30082-4
|View full text |Cite
|
Sign up to set email alerts
|

Formation of thyroid hormone revealed by a cryo-EM structure of native bovine thyroglobulin

Abstract: Thyroid hormones are essential regulators of metabolism, development, and growth. They are formed from pairs of iodinated tyrosine residues within the precursor thyroglobulin (TG), a 660-kDa homodimer of the thyroid gland, by an oxidative coupling reaction. Tyrosine pairs that give rise to thyroid hormones have been assigned within the structure of human TG, but the process of hormone formation is poorly understood. Here we report a ~3.3-Å cryo-EM structure of native bovine TG with nascent thyroid hormone form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…[16] described the structure of non-deglycosylated TG from patients without known thyroid de ciencies and the atomic model of the dimeric TG covers about 90% of the molecule. At the same time, Kim et al [15] and Marechal et al [17] reported the structure of native bovine TG at an overall resolution of 2.6 Å and 3.3 Å, respectively. These models provide high resolution information on the structural organization of domains, formed disul de bridges and hormonogenic, proteolysis, and glycosylation sites.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…[16] described the structure of non-deglycosylated TG from patients without known thyroid de ciencies and the atomic model of the dimeric TG covers about 90% of the molecule. At the same time, Kim et al [15] and Marechal et al [17] reported the structure of native bovine TG at an overall resolution of 2.6 Å and 3.3 Å, respectively. These models provide high resolution information on the structural organization of domains, formed disul de bridges and hormonogenic, proteolysis, and glycosylation sites.…”
Section: Discussionmentioning
confidence: 95%
“…The N-terminal and central region of the monomeric TG preprotein is composed of three different cysteine-rich repeat motifs called TG type 1, TG type 2 and TG type 3, whereas the región C-terminal is integrated by a non-repeat cholinesterase-like (ChEL) domain [8][9][10][11][12][13]. Recently, the 3-dimensional atomic structure of human an bovine TG has been reported [14][15][16][17] To date, more than two hundred and ninety deleterious variants in the human TG gene (loss-of-function variants or missense variants involving wild-type cysteine residues and the ChEL domain) have been reported associated to thyroid diseases, mainly to CH [18][19][20][21][22][23][24]. Several studies show that structurally defective TG mutants become trapped in the endoplasmic reticulum (ER), causing thyrocyte ER stress [25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Micrographs were processed with relion [35]. The streptavidin crystal pattern in the micrographs of the streptavidin affinity grids was erased in Fourier space using python scripts described in [36]. Particles were extracted with a binning of 4 times.…”
Section: Methodsmentioning
confidence: 99%
“…For the Rea1 ΔAAA2H2α ATPγS and Rea1 D2915A-R2976A-D3042A ATP data sets, standard copper/rhodium quantifoil R2/2 with an additional carbon layer and streptavidin affinity grids [36] were used. In addition, standard copper/rhodium quantifoil R2/2 without additional carbon layer were used for Rea1 D2915A-R2976A-D3042A ATP.…”
Section: Cryoem Electron Microscopymentioning
confidence: 99%
“…The Tg protein concludes with the Cholinesterase-Like domain (ChEL, bearing three internal disulfide bonds) plus a short unique tail sequence ( Figure 1 A). Four recent papers have provided new insight into the three-dimensional structure of Tg (two human; two bovine) by modeling from cryogenic electron microscopy [ 28 , 34 , 40 , 41 ], and schematic of the 3D structure is shown in Figure 1 B. Specifically, when the color-coded image of Figure 1 B is considered alongside the color-coded primary structure of Tg in Figure 1 A, it becomes apparent that globally, the monomer structure has an overall J-like shape, in which region I is roughly equally divided into an ‘N-terminal domain’ encoded by the first 9 exons (of a total of 48), and what has been called the ‘core domain’ is encoded by the next 7 exons.…”
Section: Tg Folding and Tg Mutations That Trigger Misfoldingmentioning
confidence: 99%